Gebyar Kompetisi Keagamaan Sebagai Sarana Aktualisasi Bakat Dan Minat Islami Anak Di Masjid Baiturrahim Kelurahan Sumur Dewa Kota Bengkulu - Intan Riftin; Bembisapta, Bembisapta; Frezy Noviardi; Ade Tria Utami; Esya Edriyani (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
A community service initiative—conducted as a Research-based Student Community Service (KKN) program by Study Program Group 18 at Baiturrahim Mosque, Sumur Dewa Urban Village, Bengkulu City—was carried out to foster children's potential and talents in Islamic religious activities. The initiative was prompted by the lack of opportunities for children to showcase their talents within the mosque environment. The "Religious Competition Festival" program was designed using the Asset-Based Community Development (ABCD) approach, which leverages the community's existing strengths. Implementation followed the Discovery, Dream, Design, and Destiny stages. Competition categories included the *adhan* (call to prayer), memorization of short Quranic chapters, and Muslim fashion. Results indicated significant improvements in the children's self-confidence, public performance courage, and sportsmanship. According to the Societal Impact Index, 87% of participants expressed satisfaction with the program. This initiative contributes to strengthening the Islamic character of the younger generation and encourages active community participation in the development of non-formal education.